Engineering of a device to remedy the mathematical difficulties of tunisians students at the entrance to the intermediate school - Rahim Kouki (Universidade Federal do Oeste da Bahia, 2020)
In this paper, we show the relevance of the intersection of the taxonomic levels introduced by Bloom (1956) and developed by Krathwohl (2002) with the knowledge implementation levels introduced by Robert (1998) for the analysis of a questionnaire in the framework of a national assessment of the achievements of Tunisian students at the entrance to the intermediate school on the one hand, and to set up a remedial device allowing teachers to appropriate the didactic tools necessary to address some of the difficulties that may be encountered by their teachers students in the formative evaluation process, on the other hand.